Pengaruh Pengalaman Kerja Dan Lingkungan Kerja Internal Terhadap Peningkatan Kualitas Pegawai Rumah Sakit Muhammadiyah Palembang (Jurnal Manajemen dan Investasi (MANIVESTASI), 2025)
ABSTRACT This study aims to determine the effect of work experience on the quality of work of Muhammadiyah Hospital Palembang employees. The population of this study were all permanent employees of muhammadiyah Hospital in Palembang. The research sample was 80 respondents taken by all of the Muhammadiyah Hospital in Palembang. The data studied were questionnaires for Muhammadiyah Hospital Palembang employees.method used quantitative method. Based on research results 1) based on the t-test of the work experience variabel there is a significan effeck of 0.000